Assessment of Conditions Influencing Agrobacteriummediated Transient Expression of uidA Gene in Leaf Disks of Sugarbeet (Beta vulgaris) - Öktem, Hüseyin Avni; Yücel, Meral (Assessment of Conditions Influencing Agrobacteriummediated Transient Expression of uidA Gene in Leaf Disks of Sugarbeet (Beta vulgaris) Journal of Genetics and Molecular Biology, 2007)
Optimum Agrobacterium-mediated transformation condition on sugarbeet (ELK345) leaf disks were examined in this study. Parameters are “vacuum infiltration, different bacterial growth medium, inoculation time with bacteria, treatment bacterial strains (EHA105, LBA4404 and GV2260) and L-cysteine in co-cultivation medium” that were studied for optimization. After 3 days, effect of these parameters on transformation was evaluated by histochemical GUS assays. Leaf disks on blue spots were quantitatively analyzed by Zeiss® KS300 image analysis platform. Transient gene expression was enhanced upto 3 fold both by vacuum infiltration at 400 mmHg and Agrobacterium strain GV2260. Selection schemes using phosphinotricin or kanamycin as selective agents were also assessed. Medium containing 150 mg/l kanamycin or 3 mg/L phosphinotricin (PPT) totally inhibited the shoot regeneration. These transformation and selection procedure may be amenable to genetic transformation and may provide a valuable tool in sugarbeet improvement programs.
Keywords: Agrobacter ium s t rains , Beta vulgar i s , kanamycin,phosphinotricin, sugarbeet, transient uidA gene expression